The Good Faith in Case of the Invalidity of the Employment Contract - Chochova, Maria (Yearbook of the Law Department, 2019)
This paper addresses some key issues related to the legal significance of the good faith of the employee in declaring invalid the grounds for employment to which he is a party. Although not exhaustive, the peculiarities of some legal consequences in case of bad faith of the employee as a party to an employment relationship, the grounds for which have been declared invalid, are also taken into account.